Loss of ARID1A activates mTOR signaling and SOX9 in gastric adenocarcinoma—rationale for targeting ARID1A deficiency. Issue 3 (30th March 2021) - Dong, Xiaochuan; Song, Shumei; Li, Yuan; Fan, Yibo; Wang, Lulu; Wang, Ruiping; Huo, Longfei; Scott, Ailing; Xu, Yan; Pizzi, Melissa Pool; Ma, Lang; Wang, Ying; et al.
Abstract : Background: Gastric adenocarcinoma (GAC) is a lethal disease with limited therapeutic options. Genetic alterations in chromatin remodelling gene AT-rich interactive domain 1A ( ARID1A ) and mTOR pathway activation occur frequently in GAC. Targeting the mechanistic target of rapamycin (mTOR) pathway in unselected patients has failed to show survival benefit. A deeper understanding of GAC might identify a subset that can benefit from mTOR inhibition. Methods: Genomic alterations in ARID1A were analysed in GAC. Mouse gastric epithelial cells from CK19-Cre-Arid1A fl/fl and wild-type mice were used to determine the activation of oncogenic genes due to loss of Arid1A. Functional studies were performed to determine the significance of loss of ARID1A and the sensitivity of ARID1A-deficient cancer cells to mTOR inhibition in GAC. Results: More than 30% of GAC cases had alterations (mutations or deletions) of ARID1A and ARID1A expression was negatively associated with phosphorylation of S6 and SOX9 in GAC tissues and patient-derived xenografts (PDXs). Activation of mTOR signalling (increased pS6) and SOX9 nuclear expression were strongly increased in Arid1A −/− mouse gastric tissues which could be curtailed by RAD001, an mTOR inhibitor. Knockdown of ARID1A in GAC cell lines increased pS6 and nuclear SOX9 and increased sensitivity to an mTOR inhibitor which was further amplified by its combination with fluorouracil both in vitro and in vivo in PDXs. Conclusions: The loss of ARID1A activates pS6 and SOX9 in GAC, which can be effectively targeted by an mTOR inhibitor. Therefore, our studies suggest a new therapeutic strategy of clinically targeting the mTOR pathway in patients with GAC with ARID1A deficiency.